A Review of UltraHigh Frequency Ultrasonic Transducers - Chen, Jun; Fei, Chunlong; Lin, Danmei; Gao, Pengkai; Zhang, Junshan; Quan, Yi; Chen, Dongdong; Li, Di; Yang, YinTang (Frontiers in Materials, 2022)
The Scanning Acoustic Microscope (SAM) has been widely concerned in recent years due to the advantages of high resolution, penetrability, and nondestructive testing, which is active in various fields, including nondestructive evaluation in the semiconductor industry, microscopic biological organization imaging in biomedicine, and so on. Ultrahigh frequency (UHF) ultrasonic transducers play a critical role in the performance of SAM, furthermore, piezoelectric materials are a key element in ultrasonic transducers. This article focuses on the topic of preparation of ultra-high frequency ultrasonic transducers, and reviews three aspects: material selection, focus design, and acoustic energy transmission matching. Provides a summary of the current research status, and puts forward some views on the future development of UHF ultrasound devices.